Nutritional Challenges and Dietary Practices of Ethnic Minority (Indigenous) Groups in China: A Critical Appraisal - Wang, Zeyuan; Mashford-Pringle, Angela (Frontiers in Sustainable Food Systems, 2022)
Indigenous food systems can affect multiple aspects of Indigenous people’s health. In China, the government declared that there are no Indigenous peoples in China and used the term ethnic minority groups instead. However, currently, no study has broadly investigated or summarized the nutrition status and dietary practices of all 55 ethnic minority groups. To start to understand this essential issue, a systematic review is required. The main selection criteria were publications should be about nutrition status or dietary practices among ethnic minority groups in China, specify the name of the ethnic minority group, and be published within the past ten years. For this literature review, 111 publications were selected. Linear regressions were applied to explore what factors can affect the total number of publications for an ethnic minority group. The main findings include that only 15 ethnic minority groups have dietary intake data representing the general people of the ethnic group; only seven ethnic minority groups have data for both nutrition status (anthropometric and nutrients intake/deficiency) and dietary practices (dietary intake and dietary habits); there are still ten ethnic minority groups with a total number of population 845,420 that lack studies on both nutrition status and dietary practices; ethnic minority groups are suffering from double-burden malnutrition and consuming imbalanced diets; the most prevalent study populations are primary and middle school students; and an ethnic minority group is likely to have more publications about nutrition status and dietary practices if the ethnic minority group has a larger population or is unique to a region. The results indicate that more national-level programs and timely nutrition and dietary reports should be implemented to address double-burden malnutrition and imbalanced diets among ethnic minority groups in China. More studies involving maternal nutrition, targeting underrepresented ethnic minority groups and age groups, and exploring traditional food systems in China are also essential to better understand and address this issue.